Competition and Fan Substitution Between Professional Sports Leagues - Tim Wallrafen; Georgios Nalbantis; Tim Pawlowski (Review of Industrial Organization, 2022)
A peculiarity in professional sports is the fact that leagues regularly hold monopoly power within their sports. However, whether and to what extent these leagues may compete with other leagues across sports is relatively unexplored. This paper contributes to the literature by analyzing competition and fan substitution in Germany, where top-tier league managers in handball, basketball, and ice hockey have recently claimed that their teams suffer from football's dominant position. Our attendance demand models confirm the existence of significant substitution effects in this setting, which suggests that leagues indeed do compete economically across sports for fan attendance .
Keywords: 330; Budget constraints; Spatial competition; Sports demand; Time constraints